Studies on covid-19 and health reflections in vulnerable territories and in favels: a systematic review - Costa, Graciane Oliveira; Mello, José André Villas Boas (Población y Salud en Mesoamérica, 2022)
The covid-19 pandemic has had various social impacts globally, however, the favelas and their communities are considered groups with greater vulnerability. In the absence of basic sanitation, precarious residences, low income or poverty, and unemployment are factors that differ in the impacts generated by covid-19 on this specific public, compared to other localities. I have these parameters established as of great concern, determined the question that is the focus of this research: What is being produced by researchers on the subject of COVID-19 in vulnerable territories and in favelas? In order to answer the research question and considering that there have been no studies that address this issue from a systematic review, this article aims to analyze the scientific production in journals indexed in the Web of Science collection on COVID-19 and favelas. As results, it is highlighted the amount of studies produced in India and in Brazil, despite few cited, and that the co-occurrence map allows to focus on the potential of the receptivity of thematic studies on populations and their local reality of vulnerability.